Валериан Васильев - Потапов Иннокентий Афанасьевич (Художник РСФСР, 1979)
Экземпляры: ИСК (20111206) / Инвентарный номер: 714430 / Цена: 1.50 / Сис.шифр: 85.153(2)-8 / Авт.знак: П 64 / ГРНТИ: 18 / ББК: 85.153(2=Рус)6-8